Postoperative Serum Changes in Calcium, Phosphorus, iPTH, CRP, IL-6, and TNF-β Levels in Patients with Secondary Hyperparathyroidism: Postoperative Serum Changes in Calcium, Phosphorus, iPTH, CRP, IL-6, and TNF-β Levels in Patients with Secondary Hyperparathyroidism - Feng, Wenjing; Xu, Runtao; Mu, Jinghui; Li, Jie; Cheng, Mingjing (Journal of Medical Biochemistry, 2025)
Aim: This research attempted to clarify clinical impact of food structure intervention based on the concept of fast track surgery on postoperative nutritional status, Serum changes in calcium and blood phosphorus levels, immune reactive parathyroid hormone (iPTH) level, serum CRP, IL-6, and TNF-β levels and rehabilitation outcomes of patients with secondary hyperparathyroidism.Methods: Fifty patients who underwent surgery in our hospital from January 2024 to December 2024 received selection and random division into control group and observation group. The control group received conventional nursing for patients and observation group received food structure intervention based on fast track surgery concept.Results: After intervention, hemoglobin and albumin levels were higher in observation group than control group; blood calcium level and calcium-phosphorus product were also higher; blood phosphorus and immune reactive parathyroid hormone levels were lower; C-reactive protein C-reactive protein, interleukin-1, tumor necrosis factor-β levels were lower; Visual Analog Scale scores were lower, medication regimen complexity scores were higher; incidence of complications was lower. To sum up, fast track surgery fast track surgery nursing can ameliorate nutritional status of patients with secondary hyperparathyroidism, facilitate postoperative recovery, attenuate postoperative complications, and ensure patients' prognosis.Conclusion: This research provides a novel insight for excellent process and model for perioperative nursing of patients with secondary hyperparathyroidism, facilitating further development of fast track surgery.
Keywords: Serum changes , calcium , blood phosphorus levels, immune reactive parathyroid hormone (iPTH) level, serum CRP, IL-6, and TNF-β levels ,Secondary hyperparathyroidism; Fast track surgery; Food structure intervention; Nutritional status; Immune stress